The cat who taught zen - Norbury, James (William Morrow, 2023)
From the author and illustrator of the international bestseller Big Panda and Tiny Dragon comes a beautifully illustrated exploration into the journeys we take for self-discovery and the connections we make along the way. In a distant city, an old cat considers himself as wise as can be, until he hears of an ancient pine far away, under the boughs of which infinite wisdom can be found. Thus, the Cat embarks on a journey deep into the forest to search for the tree. Along the way, he meets new friends--the Hare, the Magpie, the Wolf Cub, the Monkey, the Tortoise, and the Tiger--and comes across the energetic young Kitten. What wisdom does the Cat have to impart to his friends, and, perhaps more importantly, what does he still have to learn? Inspired by Zen koans, with stunning illustrations and a gentle voice, The Cat Who Taught Zen has wisdom to offer all readers.